2003
DOI: 10.4049/jimmunol.170.2.823
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase Is Regulated by IFN-γ in the Mouse Placenta DuringListeria monocytogenesInfection

Abstract: The tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase (IDO) is expressed in macrophages that have been differentiated in the presence of CSF-1 and is important in the containment of intracellular pathogens. IDO also appears to play a role in suppression of T cell responses in a variety of contexts. In the placenta, its enzymatic activity is believed to establish a chemical barrier that protects the fetal allograft from T cell-mediated immune aggression. We have studied the regulation of IDO in the ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 50 publications
3
30
0
1
Order By: Relevance
“…not encounter tryptophan starvation during the natural infection process. In contrast to what is seen with chlamydiae, IDO expression is important for clearance of Listeria monocytogenes infection of mouse placenta (31) and acute Toxoplasma gondii infection in mice (23). Clearly, the role of IDO in controlling infection in mice depends on a complex interplay between various factors, including infected tissue/cells, cytokines present in the environment, and the infecting pathogen.…”
Section: Discussionmentioning
confidence: 81%
“…not encounter tryptophan starvation during the natural infection process. In contrast to what is seen with chlamydiae, IDO expression is important for clearance of Listeria monocytogenes infection of mouse placenta (31) and acute Toxoplasma gondii infection in mice (23). Clearly, the role of IDO in controlling infection in mice depends on a complex interplay between various factors, including infected tissue/cells, cytokines present in the environment, and the infecting pathogen.…”
Section: Discussionmentioning
confidence: 81%
“…The lung can develop strong, organ-specific antimicrobial activity while at the same time limiting the potential damage inflicted on the lung parenchyma by subsequent inflammatory processes. IDO has antimicrobial properties against a variety of intracellular pathogens, such as parasites (e.g., Toxoplasma gondii) (37), bacteria (e.g., Listeria monocytogenes) (38), mycobacteria (e.g., Mycobacterium avium) (12), and viruses (e.g., cytomegalovirus) (39). The inhibition of intracellular growth of these microorganisms can occur (a) by depletion of intracellular levels of the rarest amino acid, trp, which is essential for their growth, and/or (b) by the generation of antimicrobial trp metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Type I and II IFNs were previously described as potent inducers of IDO in macrophages (37), HeLa cells (38), and placentae (39). More recently, it was demonstrated that TNF-α, together with prostaglandin E 2 (PGE 2 ), can also induce IDO in DCs (33,40).…”
Section: Figurementioning
confidence: 99%